On Revolt, Rebellion and Revolution : Navigating the Challenges of Human Conflict - Kulcsár, Dominik (New Research in the History of Western Philosophy, 2026)
Analyzing revolt, rebellion and revolution from a philosophical perspective is crucial because of philosophy's inherent flexibility either to spark conflicts or to maintain stability. Today's growing societal polarization, intolerance and demonization of "the other" are worsened by the widespread dissemination of misinformation and conspiracy theories that fuel anger and alienation. Consequently, rebellion often becomes a preferred way for individuals to pursue their self-interests, often at the expense of their communities. This anthology explores these concepts from diverse perspectives, highlighting their significance in understanding current social tensions and the potential for change or stability.